Epilepsy and attention-deficit/hyperactivity disorder in children and adolescents: An overview of etiology, prevalence, and treatment - Uliel-Sibony, Shimrit; Chernuha, Veronika; Tokatly Latzer, Itay; Leitner, Yael (Frontiers in Human Neuroscience, 2023)
Epilepsy and attention-deficit/hyperactivity disorder (ADHD) are closely connected and commonly seen in both children and adults. Each of the disorders has major psychosocial and quality of life (QOL) effects, and their co-occurrence makes coping even more challenging for both the patients and their families. Moreover, an adverse effect of some anti-seizure medications can potentially induce or exacerbate symptoms of ADHD on the one hand, while some ADHD medications may increase seizure risk on the other. The combination of proper diagnosis and appropriate treatment may improve or even prevent many of the complications associated with these conditions. The objectives of this review are to present the complex relationship between epilepsy and ADHD, looking into the pathophysiological, anatomical, and functional perspectives along with the psychosocial and QOL influences and the recommended treatment approaches in accordance with the latest literature.